2017
DOI: 10.20471/acc.2017.56.04.22
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteoprotegerin in Patients with Calcified Aortic Valve Stenosis in Relation to Heart Failure

Abstract: The aim of the study was to assess the role of serum osteoprotegerin (OPG) as a biomarker in patients with aortic valve stenosis (AS) in relation to heart failure and symptomatic status. This was a case control study, which included 51 patients with AS and 39 control subjects. At the time of study enrolment, detailed medical history was obtained and all subjects underwent physical examination, chest x-ray and echocardiography. OPG levels were measured in all subjects, and serum N-terminal of the pro b-type nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…We found low levels of OPG in mechanical prostheses; in relation, this finding has been found that low levels of OPG lead to an osteoclastic transformation of the valve, 22 and on the other hand, there is a negative correlation between native AVA and OPG. 23 Increased ET-1 and endothelin receptor-A levels have been identified in patients with native AS, 24 and endothelin A and B receptors are located on the leaflets' tips and surface.…”
Section: Valvular Heart Diseasesupporting
confidence: 72%
See 1 more Smart Citation
“…We found low levels of OPG in mechanical prostheses; in relation, this finding has been found that low levels of OPG lead to an osteoclastic transformation of the valve, 22 and on the other hand, there is a negative correlation between native AVA and OPG. 23 Increased ET-1 and endothelin receptor-A levels have been identified in patients with native AS, 24 and endothelin A and B receptors are located on the leaflets' tips and surface.…”
Section: Valvular Heart Diseasesupporting
confidence: 72%
“…We found low levels of OPG in mechanical prostheses; in relation, this finding has been found that low levels of OPG lead to an osteoclastic transformation of the valve, 22 and on the other hand, there is a negative correlation between native AVA and OPG. 23 …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that patients undergoing surgery of the aortic valve and/or thoracic aorta have a more profound immune response and are more prone to PPS. Calcified aortic stenosis has been linked with increased serum concentrations of potential inflammatory markers in previous studies ( 11 ). It would be interesting to prospectively investigate the efficacy of prophylactic treatment with colchicine or corticosteroids in this patient population, with analysis of the impact of age, sex and other comorbidities on the development of PPS.…”
Section: Discussionmentioning
confidence: 94%